Job Satisfaction Effectiveness - Khairuddin, Khairuddin; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
In any organization, human resources are very important in carrying out the activities carried out by the organization, because human resources function as a stepping stone for the organization to achieve its business success goals. This research aims to determine the influence of the work environment, integrity and work flexibility on job satisfaction with competency as an intervening variable at the Bank Indonesia Representative Office, North Sumatra Province. The results of this research are as follows: Job Flexibility has a positive and insignificant effect on Job Satisfaction with an original sample value of 0.095 and a p value of 0.316. Work Flexibility has a positive and significant effect on Competency with an original sample value of 0.427 and a p value of 0.000. Integrity has a positive and insignificant effect on job satisfaction with an original sample value of 0.085 and a p value of 0.365. Integrity has a positive and significant effect on competence with an original sample value of 0.347 and a p value of 0.002. Competency has a positive and significant effect on Job Satisfaction with an original sample value of 0.520 and a p value of 0.026. Work Environment has a positive and insignificant effect on Job Satisfaction with a value of 0.108 p value 0.272. Work Environment has a positive and significant effect on Competency with an original sample value of 0.191 and a p value of 0.032. Job Flexibility has a positive and insignificant effect on Job Satisfaction through Competency with an original sample value of 0.222 and a p value of 0.052. Integrity has a positive and insignificant effect on Job Satisfaction through Competency with an original sample value of 0.181 and a p value of 0.058. Work Environment has a positive and insignificant effect on Job Satisfaction through Competency with an original sample value of 0.100 and a p value of 0.106.